Cienfuegos’ Linguistic Anxieties. Notes on the Author’s Papers Held at the Spanish Royal Academy - Pedro ÁLVAREZ DE MIRANDA DE LA GANDARA (Cuadernos Dieciochistas)
This article looks at the relationship between Nicasio Álvarez de Cienfuegos and the Spanish Royal Academy. Cienfuegos was inducted in 1799 and remained more or less active until 1805. He had an abiding interest in linguistic questions, and his membership in the Academy give him a chance to work on both grammatical and lexicographic issues. Few of the studies ever reached the light of day, however. Here, both the published works and the unpublished manuscripts that are held in the Library and the Archive of the Spanish Royal Academy are described in detail.